2000
DOI: 10.2466/pms.2000.90.3.947
|View full text |Cite
|
Sign up to set email alerts
|

The Repeatability of Choku-Tsuki and Oi-Tsuki in Traditional Shotokan Karate: A Morphological Three-Dimensional Analysis

Abstract: The aim of the study was to quantify the repeatability of the displacement of selected body landmarks while performing two different basic karate attacks. Seven karateka (three men, four women) with different levels of training and knowledge of karate were filmed with an optoelectronic computerized instrument (sampling rate 100 Hz) that allows the three-dimensional reconstruction of the movements of selected body landmarks. Thirteen landmarks (head, hips, upper and lower limbs) were analyzed while performing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In the present study, passive markers were used to individuate two planes (head-neck and shoulders). Their actual anatomical position was not critical for the analysis, even if position was standardized using welldefined anthropometric landmarks [26]. The choice of landmarks was a compromise between biomechanical modeling (the two reference planes) and anatomical considerations (marker movement relative to skin and to underlying bone structures [18,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, passive markers were used to individuate two planes (head-neck and shoulders). Their actual anatomical position was not critical for the analysis, even if position was standardized using welldefined anthropometric landmarks [26]. The choice of landmarks was a compromise between biomechanical modeling (the two reference planes) and anatomical considerations (marker movement relative to skin and to underlying bone structures [18,30].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of landmarks was a compromise between biomechanical modeling (the two reference planes) and anatomical considerations (marker movement relative to skin and to underlying bone structures [18,30]. Indeed, for all six markers movements relative to skin were negligible [4,16,26]: not only bony prominences with a negligible subcutaneous fat layer were chosen, but also the relevant landmarks were not directly involved in head-neck motion, Similar findings have already been reported for head and mandibular motion [18,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superior anticipatory skills (Mori et al, 2002), and a faster visuoperceptual speed (Kim and Petrakis, 1998) also arise from the comparison between different skill levels. Furthermore, a comparison of techniques has also been studied (Sforza et al 2000;Gulledge and Dapena, 2008), as the force at impact (Girodet et al, 2005).…”
Section: Comparison Between Groupsmentioning
confidence: 99%
“…Doria, Veicsteinas, Limonta, Maggioni, Aschieri, Eusebi, et al (2009) found that explosive strength was not different between men and women, but attributed this to low statistical power in their study. In another study (Sforza, Turci, Grassi, Fragnito, Pizzini, & Ferrario, 2000), women performed two punching techniques in a shorter time than did men. However, studies using experienced male karate athletes indicated better neuromuscular activation during complex motor skills (Cesari & Bertucco, 2008;Sbriccoli, Camomilla, Di Mario, Quinzi, Figura, & Felici, 2010), as well as superior anticipatory skills (Mori, Ohtani, & Imanaka, 2002).…”
mentioning
confidence: 99%